Prevalence of Acute and Chronic Forms of Leukemia in Various Regions of Khyber Pakhtunkhwa, Pakistan: Needs Much More to be done! - Ahmad, Shujaat; Kifayatullah, -; Shah, Kiramat Ali; Hussain, Haya; Haq, Anwar Ul; Ullah, Abid; Khan, Asaf; Rahman, Najm Ur (Bangladesh Journal of Medical Science, 2019)
Background and objective: Leukemia is one of the fatal diseases and their morbidity and mortality rates increases day by day all over the world. This piece of research study was designed in order to find out the prevalence of different types of leukemia in Khyber Pakhtunkhwa, Pakistan during January 2015 to December 2016. Material and Method: The retrospective research study was carried out at Institute of Radiotherapy and Nuclear Medicine (IRNUM) Peshawar. A data of 400 admitted patients of leukemia were evaluated. Result: It was observed that acute leukemia (80%) was more prevalent than chronic leukemia (20%). Amongst types of leukemia, Acute Lymphocytic Leukemia (ALL) 49.5% (n=198) was more prevalent than Acute Myelogenous Leukemia (AML) 31.25% (n=125), Chronic Myelogenous Leukemia (CML) 10% (n=40) and Chronic Lymphocytic Leukemia (CLL) 9.25% (n=37) was less prevalent in this study. It was also found that leukemia was more prevalent in male patients 64.5% (n=258) as compared to females 35.5% (n=142) and male to female ratio was 1.8:1. Most of the patients were under the age of 20 years. Conclusion: Acute leukemia was more prevalent than chronic leukemia during this study in this part of the country and needs to be address. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.222-227